Japanese Teacher’s Perception of The Book Nihongo Dekiru - Budianto, Suhartawan; Ainie, Isnin; Irmayanti, Desy (Japanese Department Faculty of Cultural Science Universitas 17 Agustus 1945 Surabaya, 2024)
Textbooks are one of the factors that support the success of a learning process. With textbooks, students can understand the material being studied. On the other hand, textbooks can motivate teachers to increase their creativity in making teaching materials, so that the learning process becomes more meaningful. This research aims to determine Japanese language teachers' perceptions of the completeness of the Nihongo Dekiru book material. The Nihongo Dekiru book is a Japanese language textbook used by Muhammadiyah 3 Wage Elementary School students. This book consists of five volumes which are integrated with the previous volumes. The method used is descriptive qualitative using interview and observation techniques. The results were 1) no book instructions and evaluations were found in each book volume, 2) there were almost no learning outcomes in each book volume, and 3) supporting information, exercises, and work instructions were found in each book (teacher interviews were included in the discussion). Keywords: Japanese Student Book, Nihongo Dekiru, Teacher’s Perception